Penggunaan Biopot dan Media Tanam dalam Gerakan Go Green: Perspektif Seminar Eco-Harmony - Sumiati, Tina Endah; Affifah, Isriyanti; Annamevia, Kristy; Islaniah, Ade; Cahyaningtyas, Gita Nandini; Nisa, Khoiru (Jambura Journal of Educational Chemistry, 2024)
This research investigates the impact of the Eco Harmony Seminar: Exploring the Potential of Bioporeen, Biopot, and Growing Media on participants' knowledge of the Go Green movement and environmentally friendly practices. Utilizing a one-group pretest-posttest experimental design, the study involved 39 high school students from SMA Negeri 8 Kota Serang. The data analysis revealed a significant improvement in participants' understanding after the seminar, despite the data not meeting the normality assumption. Participants acknowledged the importance of using Go Green-based biopot and growing media, although implementation challenges such as the availability of supplementary materials were noted. In conclusion, the Eco Harmony Seminar not only enhanced participants' knowledge but also motivated them to support environmentally friendly practices. This study highlights the urgency of education and training in advancing the environmental movement and creating higher environmental awareness among the public.